Obstetrician-Gynecologists' Knowledge and Awareness on Nasoalveolar Molding in Newborns with Cleft Lip and Palate - Kevser Kurt Demirsoy; Semi Çalış; Süleyman Kutalmış Büyük (Galenos Yayinevi, 2022)
Objective: This study aimed to determine the level of knowledge and awareness of obstetrician-gynecologists (OB-GYNs) about the presurgical orthopedic treatment of newborns with cleft lip and palate (CLP).Methods: We conducted a 12-question survey by email to 532 OB-GYNs who were members of the Turkish Obstetricians and Gynaecologists Association. The participants were asked about their years in practice, region of practice, and knowledge of CLP and nasoalveolar molding (NAM).Results: A total of 141 OB-GYNs agreed to participate and completed the survey. Fifty-nine (42%) of 141 OB-GYNs had never heard of NAM treatment in newborns with CLP. Twenty-seven percent had information about NAM, and 23% referred newborns with CLP for NAM. No statistically significant difference existed in the knowledge level about the preoperative treatment of newborns with CLP between experienced and inexperienced OB-GYNs (P > .05).Conclusion: The knowledge levels of OB-GYNs about NAM were insufficient. We hope that this study will provide more effective results in OB-GYNs referring newborns with CLP for NAM.